Pengaruh Strategi Promosi Dan Word Of Mouth Terhadap Kepuasan Pelanggan Produk Kenzo Roof Di PT. Sukses Mustika Abadi Palembang - Joki, Joki; Kardinal, Kardinal (Universitas Multi Data Palembang, 2024)
The purpose of this study: (1) To find out whether the promotional strategy affects customer satisfaction of Kenzo Roof Products at PT. Sukses Mustika Abadi Palembang partially. (2) To determine whether word of mouth partially affects customer satisfaction of Kenzo Roof Products at PT. Sukses Mustika Abadi Palembang. (3) To determine whether promotional strategy and word of mouth affect customer satisfaction of Kenzo Roof Products at PT. Sukses Mustika Abadi Palembang simultaneously. This research uses the Roscoe method and with the help of SPSS25 software. The results of this study indicate that the partial test (t-test) of the promotional strategy variable (X1) and the word of mouth variable (X2) have a positive and significant effect on customer satisfaction. The simultaneous test (f-test) proves that the independent variables, namely the promotional strategy variable (X1) and the word of mouth variable (X2), have a positive and significant effect on the dependent variable in the form of customer satisfaction (Y).